Assessing the level of knowledge and practices of waste management among secondary school students/ Siti Akhtar Mahayuddin, Noor Rizallinda Ishak and Wan Akmal Zahri Wan Zaharuddin - Mahayuddin, Siti Akhtar; Ishak, Noor Rizallinda; Wan Zaharuddin, Wan Akmal Zahri (Universiti Teknologi MARA, Perak, 2024)
This study investigates the knowledge and practices of waste management among secondary school students. A survey was conducted among 258 students from a secondary school in the Perak Tengah District who were given questionnaires each to complete which included items to assess students' understanding of the principles of Reduce, Reuse, and Recycle (3R) as well as their actual implementation of these practices. However, after screening all the questionnaire forms, 233 forms were analysed and 25 forms were found to be incomplete. due to unanswered questions. The level of knowledge and practices were identified by ternary partitions (low/moderate/high) of the mean score. The partitioning value was determined by the five-point scale, with the highest value being 5.00, and it is divided into three levels: low (mean=1.00-2.33), medium (mean=2.34-3.67), and high (mean=3.68-5.00). Results indicate a high level of awareness and comprehension of 3R concepts among the students with an overall mean of 3.9, which demonstrates strong knowledge in this regard. This study reveals that a significant number of the students actively engage in recycling efforts and adopt good practices of waste management in their daily lives with an overall mean of 3.7. However, areas for improvement were identified, particularly in terms of reducing and reusing materials. These findings underscore the importance of ongoing education and awareness initiatives to promote environmentally responsible behaviours among the younger generation. Improving waste management can be achieved by incorporating lessons on responsible consumption and production (SDG No. 12) into the curriculum. This approach encourages students to adopt waste-reducing practices.